Characterization of Synthetic Humin from Solid Hydrolysate and Biochar from Hydrothermal Carbonization Products of Chicken Feather Waste - Siti Dewi Fatimah; Agus Kuncaka; Roto Roto (Universitas Gadjah Mada, 2024)
Solid hydrolysate and biochar 2:1 are synthetic humus from hydrothermal carbonization of chicken feather waste and contain humin that can be isolated by IHSS method. The recalcitrant humin is obtained in solid form. The yield of isolated humin from biochar 2:1 was 44.5%, and humin from solid hydrolysate was 12.7%. Analysis of humin by FTIR indicated the characteristics of complex functional groups. Based on the XRD and TEM tests, humin is formed from amorphous crystals with <14 nm in size and categorized as a superparamagnetic nanoparticle. The surface morphology of humin from solid hydrolysate is in the form of small spheres attached to larger particles, while humin from biochar 2:1 is smoother and has a larger surface area. This synthetic humin contains the nutrients N, O, Si, Cu, S, Mg, Zn, and K based on the EDX test quantitatively supported by AAS analysis. Characteristics of humin, which contains nutrients, are composed of amorphous crystals with complex functional groups during the hydrothermal carbonization process. Their relatively small heterogeneous molecules are stabilized by hydrophobic interactions and hydrogen bonds to form supramolecular compound associations in hour order. This humin content in synthetic humus is expected to increase its utility as a soil improver.